Increased Risk of Unfavorable Metabolic Outcome in Patients with Clinically Nonfunctioning Pituitary Adenomas - Doğan, B. A.; Tuna, M. M.; Arduç, A.; Başaran, M. N.; Küçükler, K.; Dağdelen, I.; Berker, D.; Güler, S. (Hormone and Metabolic Research, 2015)
The aim of this study was to investigate atherosclerotic risk markers in women with clinically nonfunctioning pituitary adenomas (CNFAs). Records of 47 women with CNFAs and 73 healthy women who were treated as outpatients between January 2010 and March 2014 were evaluated retrospectively. All study data were obtained from file records. Lipid parameters, mean platelet volume (MPV), total testosterone (TT), androstenedione (AS), and dehydroepiandrostenedione sulfate (DHEAS) were recorded. Insulin resistance (IR) was calculated with homeostatic model assessment-insulin resistance (HOMA-IR). Among the atherosclerotic risk markers, the HOMA-IR and AS levels were higher in patients with CNFAs than in healthy subjects (p=0.003, p=0.021, respectively). A positive correlation between AS and insulin/HOMA-IR levels was found among the metabolic parameters in the patients with CNFAs (p=0.001, r=0.550, p=0.004, r=0.498, respectively). The data showed that patients with CNFAs had high atherosclerotic risk markers such as insulin resistance and hyperandrogenemia. Insulin resistance may also cause hyperandrogenemia in patients with CNFAs.
Keywords: androgens; atherosclerotic risk markers; clinically nonfunctioning pituitary adenomas